Oar blade power output and boat velocity in context of rower leg, knee and trunk coordination in sculling - Baten, C.; Baten, M.; Vuijk, F.; van Hout, L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to test the feasibility of a method estimating oar power output and boat velocity in relation to rower coordination in terms of kinematics of knee, trunk and elbow, derived from a set of 17 wireless Inertial Magnetic Measurement Units (IMMUs) positioned on rower body segments, oars and boat, recorded in actual on water varsity rowing at competition speed. Although in these experiments no 2nd method was present for absolute validation, the practical feasibility, the repeatability within bouts, between similar bouts as well as the consistencies in similarities and differences between different bouts and different rowers support the feasibility of a future coach supporting tool based on this technology.